PERAN SAVE THE CHILDREN DALAM MENANGANI KASUS CHILD TRAFFICKING DI INDIA TAHUN 2017-2020 - Zikra Dhiyamas Zhafira; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Child trafficking represents a problem that is quite difficult for developing countries to deal with. One of the is India. India became a transit country, a destination, and a country of origin for child trafficking country. Economic, social and cultural are the main factors leading to the still high incidence of child trafficking in the country. The Indian government which is the main actor in protecting children, has tried to handle child trafficking, but the Indian government needs help from other actors in dealing with the problem. Save the Children is present as an International Non-Governmental Organizations (INGOs) concerned with children’s rights and seeking to fight for children’s rights in India and engage in child trafficking handling and assist the Indian government in handling the case.The study aims to find out how Save the Children plays in dealing with child trafficking in India.Then the theory used is the theory of Non-Governmental Organizations from David Lewis which explains the role of NGOs as implementers, catalysts and partners. With the above background, the author uses the concept of human security where every individual has the right to freedom and feel safe.The results of the research from this thesis are that Save the Children carries out its role in dealing with child trafficking through the role of prevention and rescue of victims. Save the Children was able to carry out its role as an NGO in dealing with child trafficking in India despite experiencing several obstacles.  Keywords        : Save the Children, Child Trafficking, India,  Non-Governmental Organizations (NGOs)